Radiological evaluation of kyphoplasty with an intravertebral expander after osteoporotic vertebral fracture. Issue 2 (27th December 2018) - Arabmotlagh, Mohammad; Nikoleiski, Sabrina C.; Schmidt, Sven; Rauschmann, Michael; Rickert, Marcus; Fleege, Christoph
ABSTRACT: Spinal deformities due to osteoporotic vertebral compression fractures can be reduced by balloon kyphoplasty, but the correction may be partly lost when the balloon is deflated. The present study aimed to evaluate an intravertebral expander developed to reduce and maintain vertebral body height while cement is injected to correct spinal deformities due to osteoporotic vertebral fractures. The study included 31 osteoporotic vertebral body fractures in 31 patients, classified as A1 according to the AO classification, who underwent kyphoplasty using an intravertebral expander. The kyphosis angle was significantly corrected from 13.4 degrees prior to kyphoplasty to 10.8 degrees ( p  < 0.01) after surgery, but this correction was lost at 12 months (13.3 degrees). The correction of the kyphosis angle best correlated with the pre‐operative mobility of the fracture ( r  = 0.59, p  < 0.01), and the loss of the kyphosis improvement correlated with the amount of correction ( r  = 0.49, p  = 0.01). All patients, except for six with adjacent vertebral fractures, experienced significant pain reduction (VAS 8.7 pre‐operatively and 2.0 at 12 months; p  < 0.01), and the pain was not affected by the correction of the spinal deformity or the loss of correction in the follow‐up period. These results suggest that the mobility of the fracture mainly determines the extent of deformity correction rather the device used for reduction, and greater corrections are at increased risk for losing the improvement. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:457–465, 2019.